Penerapan Senam Rematik Pada Pasien Osteoartritis Dengan Masalah Keperawatan Nyeri Kronis - Salsabila Syahfitri; Armi Mawaddah (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Osteoarthritis is a degenerative disease and a significant contributor to life years with an imbalance between multifactorial musculoskeletal conditions that is often found in the elderly population, especially those aged over 65 years. The purpose of this writing is to be able to carry out nursing care for osteoarthritis patients with chronic pain nursing problems to reduce pain. The method used is to carry out Rheumatic Gymnastics for 10 days in 5 visits, namely on April 22-30 2024. The place where this activity is carried out is in the Mabar Hilir Environment. Based on the evaluation results, it was found that there is an effect of rheumatic gymnastics to help reduce chronic pain In osteoarthritis patients, the pain scale goes from 7 to 3. The conclusion of this paper shows that the patient is able to do rheumatic exercises and can reduce pain in the knee and waist joints. It is hoped that the results of this research can be used as a medical intervention to reduce chronic pain in osteoarthritis patients in the community.